The RAMONA project and potential linkages to the ILRI platform - Griffiths, Patrick (European Space Agency, 2024)
A presentation on the rangeland monitoring initiative RAMONA, made at the GEF-funded STELARR project meeting 24-24 October, 2023 on a global rangelands data platform, developed by ILRI and partners.